2012
DOI: 10.4103/2229-5151.97271
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation of bone remodelling

Abstract: Remodeling, a continuous physiological process maintains the strength of the bones, which maintains a delicate balance between bone formation and resorption process. This review gives an insight to the complex interaction and correlation between the bone remodeling and the corresponding changes in host immunological environment and also summarises the most recent developments occuring in the understanding of this complex field. T cells, both directly and indirectly increase the expression of receptor activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…Under conditions of chronic inflammation, RANKL-mediated osteoclastogenesis is enhanced by oxidative stress and proinflammatory molecules including tumor necrosis factor (TNF) [ 33 ], interleukin- (IL-) 1, IL-6 [ 13 ], nitric oxide (NO) [ 34 ], and lipopolysaccharide (LPS) [ 32 ]. In this study, we investigated the direct effects of these compounds on osteoclast precursors and mature osteoclasts in the presence of RANKL under inflammatory conditions through Pg LPS induction, and we found that both AcE and Qt were able to suppress osteoclast differentiation and activity even in the presence of RANKL/ Pg LPS in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of chronic inflammation, RANKL-mediated osteoclastogenesis is enhanced by oxidative stress and proinflammatory molecules including tumor necrosis factor (TNF) [ 33 ], interleukin- (IL-) 1, IL-6 [ 13 ], nitric oxide (NO) [ 34 ], and lipopolysaccharide (LPS) [ 32 ]. In this study, we investigated the direct effects of these compounds on osteoclast precursors and mature osteoclasts in the presence of RANKL under inflammatory conditions through Pg LPS induction, and we found that both AcE and Qt were able to suppress osteoclast differentiation and activity even in the presence of RANKL/ Pg LPS in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These include interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF) [ 11 ], interferon-gamma (IFNg), interleukin-6 (IL-6), and, very importantly, RANKL that directly induces osteoclastogenesis [ 12 ]. Conversely, other cytokines such as IFN- γ , IL-3, and IL-4 can act as osteoclastogenic inhibitors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune system senses alteration in the environment, for instance damaged or aged cells [72,73], expressing Toll-like receptors and other pattern-recognition receptors (PRRs). During fracture healing, both the cells of the innate and the adaptive immunity are involved, and immune cells play essential roles during all the fracture healing phases [74][75][76][77]. The initial inflammatory reaction ensuing upon hematoma formation initiates the healing cascade and thus can significantly affect the healing outcome [33,34].…”
Section: The Initial Inflammatory Phasementioning
confidence: 99%
“…The alveolar bone in the periodontal complex is the part of the maxilla or mandible for the teeth and is a dynamic tissue for adapting architectures and generating responses against biomechanical stimulation from tooth locomotion, mastication, and occlusion, which can be transmitted from the teeth and PDLs [ 16 ]. Therefore, tooth movements are significantly associated with the rapid remodeling (formation–resorption) of alveolar bone tissues and are continuously performed to generate the homeostatic balance between resorption by osteoclastic cells and apposition by osteoblastic cells [ 18 , 19 ]. As a result of bone remodeling processes, the mineral density of the alveolar bone surrounding the teeth can have a lower mechanical stiffness than basal bone structures [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tooth movements are significantly associated with the rapid remodeling (formation–resorption) of alveolar bone tissues and are continuously performed to generate the homeostatic balance between resorption by osteoclastic cells and apposition by osteoblastic cells [ 18 , 19 ]. As a result of bone remodeling processes, the mineral density of the alveolar bone surrounding the teeth can have a lower mechanical stiffness than basal bone structures [ 18 , 19 ]. Moreover, interfacial structures, which are the mineralized tissues on the socket surfaces between the alveolar bone and the PDL regions, can be used as anchorage of Sharpey’s collagenous fiber bundles of the PDLs to form hierarchical architectures for systematic tooth-supporting functions [ 1 , 3 , 20 ].…”
Section: Introductionmentioning
confidence: 99%